2013
DOI: 10.1007/s12550-013-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of five Fusarium toxins in corn-Dried Distiller’s Grains with Solubles in Thailand and comparison of ELISA and LC-MS/MS for fumonisin analysis

Abstract: Dried Distiller's Grains with Solubles (DDGS), a by-product of bio-ethanol production from maize and other cereals, is increasingly used as a feed additive. In this study, five Fusarium toxins, including fumonisin B1 (FB1), fumonisin B2 (FB2), deoxynivalenol (DON), zearalenone (ZEN) and beauvericin (BEA) were quantified by LC-MS/MS in 59 corn-DDGS samples. In addition, the fumonisin level in 30 randomly selected-samples was compared using an ELISA detection technique. No sample was free from mycotoxin contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In Finnish samples of grain-based products, concentrations of enniatins were found to have a statistically significant correlation with moniliformin concentrations (Jestoi et al, 2004b). Beauvericin was also found in all fumonisins-contaminated samples (99 %) of maize-dried distiller's grains with solubles from Thailand (Tansakul et al, 2013) and in all fumonisins-contaminated samples (96 %) of maize and poultry feed from Brazil (Mendes de Souza et al, 2013). Boutigny et al (2012) also reported a significant correlation between beauvericin and moniliformin levels in maize from South Africa.…”
Section: Co-occurrence Between Beauvericin and Enniatinsmentioning
confidence: 99%
“…In Finnish samples of grain-based products, concentrations of enniatins were found to have a statistically significant correlation with moniliformin concentrations (Jestoi et al, 2004b). Beauvericin was also found in all fumonisins-contaminated samples (99 %) of maize-dried distiller's grains with solubles from Thailand (Tansakul et al, 2013) and in all fumonisins-contaminated samples (96 %) of maize and poultry feed from Brazil (Mendes de Souza et al, 2013). Boutigny et al (2012) also reported a significant correlation between beauvericin and moniliformin levels in maize from South Africa.…”
Section: Co-occurrence Between Beauvericin and Enniatinsmentioning
confidence: 99%
“…If a study reported ELISA and HPLC or GC MS/MS results for the same samples, it was assumed that the latter methods yielded more accurate levels than the ELISA technique (e.g. Tansakul et al 2013). These and additional uncertainties have been summarised in detail in a subsequent section in this study.…”
Section: Estimation Of the Mycotoxin Contamination Levels And Their Imentioning
confidence: 99%
“…The mean BEA concentration was higher in swine (0.74 μg/g) and dairy cattle (0.72 μg/g) feeds than in beef cattle (0.43 μg/g) and chicken (0.37 μg/g) feeds. BEA is also detected in Irish farm silages (21.8 μg/kg) (McElhinney et al, 2015 ) and corn-dried distiller's grains in Thailand (350 μg/kg) (Tansakul et al, 2013 ).…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%